Pergeseran Kebijakan Tata Ruang Kota Semarang 1975-2011: Dari Pembangunan Sektoral Menuju Keterpaduan Ruang - Nugraha, M. Luthfi; Mardiansjah, Fadjar Hari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Development process in a city should not be separated from the spatial planning. Therefore, spatial planning policy is always shifting and improving every time. Based on research by Lisdiono (2008), mostly the policy shifting is happened because of influence from the investor in the development. A research used for identifying the spatial planning policy shifting is needed in Semarang in order to make sure that the policy shifting is happened because of those policies are need to be improved as a result of the planning process. The metodology of the reasearch is qualitative research to identifiying path dependence phenomena, to reveal the policy shifting process by the literature, regulation, and document review, with the depth interview with the key person and the other actor that involve in the spatial planning formulation in each planning period. The result are the spatial planning policy shifting is caused by several things, i.e. : policy shifting on spatial planning guidance, national and regional policy focus adjusment, and the city development. Beside that, it is also known that there is a gap between spatial planning policy and its implementation. Spatial planning policy shifting can be used for consideration in formulating the policies in the future.